Anisakis simplex - Nagasawa, K.; Moravec, F. (Zenodo, 2002)
Anisakis simplex (Rudolphi, 1809) (®gure 2) Third-stage larva ( W ve specimens). Body 21 820±27 320 long and 412±474 wide; cuticle with very ®ne transverse striations. Cephalic end rounded, with prominent ventral cuticular tooth; latter 8±10 long, ventrally bent, sharply pointed. Anlagen of lips weakly developed. Oesophagus almost cylindrical, muscular, light-coloured, 1730±2580 long. Nerve ring 305±392 from anterior extremity. Ventriculus long, 960±1480, width 209±287, its posterior end obliquely shaped in lateral view. Renette cell very long, darkly coloured, extending anteriorly along ventral side of intestine to level of posterior end of ventriculus; excretory canal narrow, colourless, opening in excretory pore situated below ventral cephalic tooth. Intestine straight. Rectum short, hyaline; three small round unicellular rectal glands present. Tail rounded, 100±157 long, ending in sharp cuticular spike 12±20 long. Hosts. Onychoteuthis borealijaponica Okada, 1927 (Onychoteuthidae) and Gonatopsis borealis Sasaki, 1920 (Gonatidae). Site of infection. Encapsulated in stomach wall. Localities. Central North Paci®c Ocean (42ss39¾N, 179ss30¾W and 43ss39¾N, 179ss30¾W, both 23 June 1993 Ð O. borealijaponica 44ss39¾N, 179ss30¾W, 24 June 1993 Ð G. borealis ) and western North Paci®c Ocean (41ss20¾N, 147ss00¾E, 12 May 1982 Ð O. borealijaponic a ). Voucher specimens deposited. National Science Museum, Tokyo (NSMT, as 2935 to 2937) and Institute of Parasitology, ASCR, C ÏeskeÂ BudeÏjovice (Cat. No. N-617). Comments Larvae of the present material are morphologically identical with those reported by Nagasawa and Moravec (1995) from the Japanese common squid, Todarodes japonicus Steenstrup, of the Sea of Japan, but their body size and measurements are generally somewhat smaller, which may be considered an intraspeci®c variability. In the western North Paci®c Ocean, A. simplex larvae were reported from three species of squid hosts, T. paci W cus , O. bartramii and O. borealijaponica (Oshima, 1972; Bagrov, 1982; Kurochkin and Solov’eva, 1982), but there are no records of this parasite from squids in the central North Paci®c Ocean. Adult A. simplex is a parasite mainly of cetaceans and pinnipeds in cold temperate and polar waters (Davey, 1971; Kuramochi et al ., 1996) and conspeci®c third-stage larvae occur largely in various ®sh species, but also crustaceans, cephalopods and some other invertebrates (Nagasawa, 1990b). This species is known as the main agent of human anisakiosis. : Published as part of Nagasawa, K. & Moravec, F., 2002, Larval anisakid nematodes from four species of squid (Cephalopoda: Teuthoidea) from the central and western North Paci ® c Ocean, pp. 883-891 in Journal of Natural History 36 (8) on pages 885-886, DOI: 10.1080/00222930110051752, http://zenodo.org/record/5300179 : {"references": ["NAGASAWA, K. and MORAVEC, F., 1995, Larval anisakid nematodes of Japanese common squid (Todarodes paci W cus) from the Sea of Japan, Journal of Parasitology, 81, 69 \u00b1 75.", "OSHIMA, T., 1972, Anisakis and anisakiasis in Japan and adjacent areas, in K. Morishita, Y. Komiya and H. Matsubayashi (eds) Progress of Medical Parasitology in Japan, Vol. 4 (Tokyo: Meguro Parasitological Museum), pp. 301 \u00b1 393.", "BAGROV, A. A., 1982, On infection rate of squids in the North Paci \u00ae c by anisakid larvae (Nematoda, Anisakidae), Parazitologiya, 16, 200 \u00b1 203 (in Russian with English abstract).", "DAVEY, J. T., 1971, A revision of the genus Anisakis Dujardin, 1845 (Nematoda: Ascaridata), Journal of Helminthology, 45, 51 \u00b1 72.", "KURAMOCHI, T., MACHIDA, M., ARAKI, J., UCHIDA, A., KISHIRO, T. and NAGASAWA, K., 1996, Minke whales (Balaenoptera acutorostrata) are one of the major \u00ae nal hosts of Anisakis simplex (Nematoda: Anisakidae) in the northwestern North Paci \u00ae c Ocean, Reports of the International Whaling Commission, 46, 415 \u00b1 419.", "NAGASAWA, K., 1990 b, The life cycle of Anisakis simplex: a review, in H. Ishikura and K. Kikuchi (eds) Intestinal Anisakiasis in Japan: Infected Fish, Sero-immunological Diagnosis, and Prevention (Tokyo: Springer-Verlag), pp. 31 \u00b1 40."]}